HADIS ASPEK KEJIWAAN DALAM PROSES BELAJAR (KAJIAN PSIKOLOGI ISLAM) - Muhammad Ali; Nurul Iqram Asdar (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2022)
Success in studying is not only determined by basic abilities, but this is also related to the process or way of learning. The human psyche in learning is different so that understanding the psychological aspects in the learning process has an important position in achieving results. This research is a library research, by collecting related literature, then it is presented in a qualitative descriptive manner, namely displaying the data as it is using a psychological approach. Based on the hadith of the Prophet about the psychological aspect in the learning process provides an understanding that the strategic steps that are prepared to carry out a learning and effort, namely choosing the right time to convey advice and knowledge to the ummah or friends so as not to get bored, are known as situational and conditional methods. Using an emotional or psychological approach is an attempt to understand and live up to intelligence, interests and talents as well as being able to feel what is good and what is bad so as to be able to provide motivation or advice that can be well received.